Unmasking the gossipy chat: Co-operativeness in all-female conversations - Balgos, Anne Richie G. (Animo Repository, 2013)
Many linguists have embarked on looking into gender as a research variable because men and women have their unique way of using language especially when in single-sex groups. However, a gendered conversational style may be contextualized by looking into the task, topic, and other discourse variables. Over time, women-interaction has crafted a positive definition for gossip-the talk among women in their common role as women. This paper analyzes topic development and turn-taking patterns in all-female conversations across age groups. In addition, it examines how these features contribute to female cooperation in gossip.